Peripheral Ulcerative Keratitis: A Serious Corneal Inflammation: Poster Presentation - Case Report - Resident - Fitrah; Havizra Vitresia; Getry Sukmawati (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Peripheral ulcerative keratitis (PUK) is a rare, but severe sight-threatening inflammatory condition that affects the cornea. PUK is characterized by peripheral corneal ulceration, stromal thinning, and neovascularization that can lead to corneal perforation and vision loss. Although PUK can occur in individuals without underlying systemic disease, it is most commonly associated with autoimmune disorders. Case Illustration : A 53-year-old woman presented to the ophthalmology clinic with complaints of redness, foreign body sensation, and blurred vision in her both eye for the past three days. On examination, slit-lamp biomicroscopy revealed a peripheral corneal ulcer. She had a history of rheumatoid arthritis for the past 2 months and was being treated with methotrexate and metylprednisolone. Laboratory investigations revealed elevated Anti-CCP IgG, which confirmed the presence of rheumatoid arthritis. Discussion : PUK is most commonly associated with autoimmune disorders, particularly rheumatoid arthritis, but may also occur in individuals with infectious, degenerative or traumatic corneal injuries. Immune- mediated inflammation, complement activation, and tissue destruction are thought to be involved in the pathogenesis of PUK. The diagnosis of PUK requires a thorough ophthalmic examination, including slit-lamp biomicroscopy, and laboratory investigations for underlying autoimmune disorders. Conclusion : PUK is a rare but serious ocular disease that requires prompt diagnosis and management to prevent severe complications such as corneal perforation and vision loss. Although PUK can occur in individuals without underlying systemic disease, it is most commonly associated with autoimmune disorders, particularly rheumatoid arthritis.